PKM MESIN PENGIRIS BAWANG UNTUK USAHA BAWANG GORENG DESA KARYA MAKMUR KABUPATEN BANGKA - Husman, Husman; Idiar, Idiar; Napitupulu, Robert; Fadhlurrahman, Miftah; Akbar, Muhammad; Haikal ikhsan, Muhammad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Fried onions made from shallots are an important type of horticultural crop and are very often used by the public. The process of making fried onions is carried out in several stages until it becomes fried onions that are ready to be consumed, starting from peeling the onion skin, slicing, frying, draining and packing. From the results of a survey conducted on partners, the process of slicing onions is still done manually using a slicing tool made of wood. Mrs. Yuliana, who currently produces fried onions, reaches 10 kg/day for Monday - Thursday, and Friday - Sunday 15-20 kg/day, and for religious holidays usually the capacity produced can reach 60 kg/day, with a total on average 500 kg per month, you have to replace the slicer every 4 months. The tool currently used to slice onions has a capacity of 10 kg/hour, so it requires more energy and time for the slicing process. In order to increase the production of shallots and produce slices as is done today, a shallot slicing machine was developed with a slicing system similar to the tool used. Partners receive appropriate technology in the form of shallot slicing machines and training on the process of using the machine and maintaining the machine. Apart from that, a monitoring and evaluation process is also carried out to measure the level of success and obstacles to the machines used by partners. After developing a red onion slicing machine, partner production productivity increased, the machine can function well and is capable of peeling 2.5 kg of red onion skin in 4 minutes in one process or 37.5 kg/hour.